STOCK MARKET REACTIONS TO THE FIRST FINANCIAL REPORTING IN IFRS OF BRAZILIAN BANKING SECTOR: AN EVENT STUDY - Fé Jr., Armando Lopes Dias; Nakao, Sílvio Hiroshi; Ribeiro, Maísa de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
Traded Brazilian banks are required to report consolidated financial statements since 2010 in two different accounting standards sets: COSIF (issued by Central Bank of Brazil) and IFRS. Since the first IFRS report, for the year 2010, was issued after the reporting of financial statements in COSIF, this paper verified the stock market reactions around the moment of the reporting in IFRS, thus isolating the effect of incremental information regarding what had been presented in COSIF. The event study revealed the existence of cumulative abnormal returns (CAR) between -10.2% and +4.01%, suggesting that the adoption of IFRS was value relevant to the analyzed banks. We also found that CAR were influenced by risk measured by Beta in the event window around IFRS reporting. These results suggest that the reporting under IFRS by the analyzed Brazilian banks brought value relevant information and may have increased investors' assessment of risk.